Are we teaching citizenship right? : A critical review of Pancasila education textbooks - Isnariah; Rizwan, Feri; Marzuki (Universitas Negeri Yogyakarta, 2025)
This study aims to analyse the content and frequency of civic competence components found in the main textbook (Buku Teks Utama/BTU) for Grade IX Pancasila Education, published in 2023 by the Ministry of Education, Culture, Research, and Technology of Indonesia. Civic competence, which encompasses knowledge, skills, values, attitudes, and character, is a critical domain in the formation of democratic and responsible citizens. This research adopts a mixed-methods content analysis that integrates both qualitative and quantitative approaches to examine how these components are presented and distributed throughout the textbook. Data collection involved a systematic process of reading, coding, and recording relevant content, allowing for an in-depth evaluation of textual material. The analysis reveals three major findings. First, the main textbook for Grade IX includes all core components of civic competence, with each aspect represented in various learning sections. Second, the knowledge component is the most dominant, accounting for 49.18% of the total civic competence content, indicating a strong emphasis on cognitive learning outcomes. Third, the main textbook presents these components through structured pedagogical features such as introductions to learning, instructional materials, learning activities, reflective tasks, and assessment instruments. These findings suggest that while the textbook supports the development of civic competence, there is a disproportionate focus on knowledge-based content compared to affective and behavioural dimensions. The study offers insights into the current orientation of Pancasila education and provides recommendations for balancing cognitive and character-based competencies to strengthen civic education in Indonesia’s formal curriculum.